2013
DOI: 10.1200/jop.2012.000595
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Venous Thrombosis in Patients With Cancer With Peripherally Inserted Central Venous Catheters: A Retrospective Analysis of Risk Factors

Abstract: Purpose: Peripherally inserted central catheters (PICCs) are often used in place of mediport catheters because of cost and lack of operating room time and to prevent delays in therapy. One common complication associated with their use is upper extremity venous thrombosis (UEVT). The purpose of this study was to ascertain risk factors associated with an increased risk of PICCassociated UEVT in patients with cancer. Methods Conclusion:Specific factors significantly increase the risk of UEVT in patients with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 28 publications
2
39
2
2
Order By: Relevance
“…This finding is attributed to the higher incidence of chemotherapy-induced thrombocytopenia [13]. Many risk factors for PICC-related thrombosis were analyzed in several studies such as obesity, gender, history of DVTs and use of anticoagulation but none were conclusive and only revealed conflicting results [14][15][16][17]. In our study, only younger age at insertion of PICC was associated with higher risk of thrombosis.…”
Section: Discussioncontrasting
confidence: 31%
“…This finding is attributed to the higher incidence of chemotherapy-induced thrombocytopenia [13]. Many risk factors for PICC-related thrombosis were analyzed in several studies such as obesity, gender, history of DVTs and use of anticoagulation but none were conclusive and only revealed conflicting results [14][15][16][17]. In our study, only younger age at insertion of PICC was associated with higher risk of thrombosis.…”
Section: Discussioncontrasting
confidence: 31%
“…Low molecular weight heparin therapy was instituted followed by oral anticoagulation. A study done by Patel GS et al revealed the incidence of venous thrombosis associated with PICCs as 25 % while another study by Ahn DH et al reported venous thrombosis associated with PICC in 15 % of the patients [9,10]. Jumani K et al described the incidence of mechanical complications in 16.4 % of the cases [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is retrospective in nature with problems of incomplete documentation. Relevant factors that may contribute to PICC‐related AEs, such as the number of lumens, length of hospital stay, comorbidities (i.e., obesity, diabetes, malnourishment, hypercoagulability status), surgery, use of erythropoiesis‐stimulating agents, chemotherapy regimen, and flushing practices, were not collected . The diagnosis of PICC‐associated thrombosis was exclusively clinical, based on symptoms such as lack of compressibility of the veins, edema, and erythema.…”
Section: Discussionmentioning
confidence: 99%